Sulfamethoxazole-Altered Transcriptomein Green Alga Raphidocelis subcapitata Suggests Inhibition of Translation and DNA Damage Repair - Guo, Jiahua; Zhang, Yibo; Mo, Jiezhang; Sun, Haotian; Li, Qi (Frontiers in Microbiology, 2021)
Occurrence of sulfonamide antibiotics has been reported in surface waters with the exposures ranging from < 1 ng L–1 to approximately 11 μg L–1, which may exert adverse effects on non-target algal species, inhibiting algal growth and further hindering the delivery of several ecosystem services. Yet the molecular mechanisms of sulfonamide in algae remain undetermined. The aims of the present work are: (1) to test the hypothesis whether sulfamethoxazole (SMX) inhibits the folate biosynthesis in a model green alga Raphidocelis subcapitata; and (2) to explore the effects of SMX at an environmentally relevant concentration on algal health. Here, transcriptomic analysis was applied to investigate the changes at the molecular levels in R. subcapitata treated with SMX at the concentrations of 5 and 300 μg L–1. After 7-day exposure, the algal density in the 5 μg L–1 group was not different from that in the controls, whereas a marked reduction of 63% in the high SMX group was identified. Using the adj p < 0.05 and absolute log2 fold change > 1 as a cutoff, we identified 1 (0 up- and 1 downregulated) and 1,103 (696 up- and 407 downregulated) differentially expressed genes (DEGs) in the 5 and 300 μg L–1 treatment groups, respectively. This result suggested that SMX at an environmentally relevant exposure may not damage algal health. In the 300 μg L–1 group, DEGs were primarily enriched in the DNA replication and repair, photosynthesis, and translation pathways. Particularly, the downregulation of base and nucleotide excision repair pathways suggested that SMX may be genotoxic and cause DNA damage in alga. However, the folate biosynthesis pathway was not enriched, suggesting that SMX does not necessarily inhibit the algal growth via its mode of action in bacteria. Taken together, this study revealed the molecular mechanism of action of SMX in algal growth inhibition.